2013
DOI: 10.3851/imp2562
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Virological Failure in HIV-Infected Children on Antiretroviral Therapy in Rural Cameroon: A Cross-Sectional Study

Abstract: This study demonstrates high virological failure rates and a high variability of NVP plasma levels among HIV-infected children in a routine ART programme in rural Cameroon. Strategies to improve adherence to ART in HIV-infected children are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
6
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 47 publications
(57 reference statements)
11
36
6
4
Order By: Relevance
“…Our finding was in line with study conducted in Cameron [28] and in Gondar, Ethiopia [26] showed long time duration of treatment to be one of determinant factors for treatment failure.…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 92%
“…Our finding was in line with study conducted in Cameron [28] and in Gondar, Ethiopia [26] showed long time duration of treatment to be one of determinant factors for treatment failure.…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 92%
“…A study conducted in Cameroon showed that risk of virological failure was substantially increased if the child's mother had already died [14]. Sebunya et al found that Ugandan children who never experienced ART failure were more likely to have a grandmother as their primary caregiver and suggest that grandparents often reside in rural settings and have more time to offer care to the children, facilitating adherence [16].…”
Section: Resultsmentioning
confidence: 97%
“…When patients initiating ART fail to achieve viral suppression by 24 weeks of treatment, the possibility of suboptimal adherence and other factors must be considered. Treatment failure, as measured by detectable viral load (VL) during chronic care, has been shown to be associated with non-adherence [14][15][16], although this has not been consistently observed [17]. In a study from Zambia, Haberer et al demonstrated that older children (9-15 years) who were unaware of their HIV diagnosis were at risk of treatment failure due to poor adherence [18].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Its continued positive clinical impact depends on taking more than 95% of prescribed doses (Jobanputra et al, 2015;WHO, 2013;Zoufaly et al, 2013;Bhattacharya & Dubey, 2011;MOH, 2007). Several factors affect the rate of treatment adherence among children including drug regimen, caregivers, and society and culture related factors (Castro, Gonzalez, & Perez, 2015;Haberer & Mellins, 2009) (Hagstromer, Lundstedt, Balcha, & Bjorkman, 2013;Muller et al, 2011), (Reda & Biadgilign, 2012).…”
Section: Introductionmentioning
confidence: 99%